Revisiting Choanal Atresia:Diagnosis And Evolving Treatment Paradigms - Pandey, Rajesh; Kumar Pathak, Aditya; Kumar Gupta, Jitendra (Journal of Neonatal Surgery, 2025)
Background: Choanal atresia is a congenital obstruction of the posterior nasal passage, presenting with that of the significant clinical challenges. This particular condition can be unilateral or bilateral, often each are mainly causing airway obstruction in neonates and infants. Objective: To review the diagnostic techniques, as well as evolving treatment paradigms for choanal atresia, with an actual emphasis on modern advancements in that of the surgical as well as the non-surgical management.. Methods: A systematic literature assessment was carried out using PubMed, Scopus, and Google Scholar for articles published between 2000 and 2024. Studies specializing in diagnostic methodologies, and evolving treatments for choanal atresia had been protected. Results: Current remedy strategies variety from endoscopic surgical procedure to modern non-invasive methods (Purrinos et al., 2023). While early surgical intervention is considered preferred, new strategies such as transnasal endoscopic restore have improved results with reduced complication costs. Advanced imaging techniques are revolutionizing analysis. Conclusion: Choanal atresia remains an important circumstance requiring active diagnosis and intervention. Emerging treatment paradigms continue to improve prognosis, even though long-term observation-up care is critical for preventing complications.